Tribological Performance of Polymer Composite Modified with Calcined Eggshell Particles Post High-Temperature Exposure - Sunardi Sunardi; Dody Ariawan; Eko Surojo; Aditya Rio Prabowo; Tohid Ghanbari-Ghazijahani; Cahyo Hadi Wibowo; Hammar Ilham Akbar (Ital Publication, 2024)
During operation, brake lining material rubs against the disc to generate heat. This heat could decrease the brake lining performance, such as the friction coefficient, specific wear rate, and interface temperature of the rubbing surfaces. The resulting wear debris is environmentally harmful and poses risks to human health. Therefore, this study aimed to replace the harmful material using eggshell particles as a filler in brake lining composite and enhance tribological properties. The brake lining samples were manufactured through three stages: cold compaction, hot compaction, and post-curing. The next step is the samples were subjected to a one-hour high-temperature exposure at 200°C, 300°C, 400°C, and 500°C. The results showed that the high-temperature exposure significantly affected the specific wear rate, friction coefficient, and interface temperature between the brake lining and disc. An interesting finding was that adding calcined eggshell particles in composite could improve the tribological properties up to 400°C. However, the best material’s performance resulted when the samples got an exposure temperature of 200°C. Doi: 10.28991/ESJ-2024-08-04-03 Full Text: PDF